SIMULATION OF SEA SHIPS AGENCY SERVICE PROCESS - Drozhzhyn , Oleksii; Koskina, Yuliia (Science-based technologies, 2024)
The paper searches the work process of a ship agent - providing a set of representation services and ensuring compliance with the interests of a vessel located in a sea port for the purpose of loading/discharging of cargo and/or for other purposes. Agents organize and coordinate the arrival, staying and departure of vessels from the seaport. In the paper, the agency service of ships in sea ports is presented as one consisting of three stages of the work of a ship agent - operations that are carried out before the arrival of the vessel in the port, during the stay of the vessel in the port and after her departure. The events that fixed the beginning and end of each stage are defined. The agency service process is rather complex due to the large number of third parties to be involved in the procedures and formalities that allow a vessel to arrive in the port and depart. Such a process is accompanied by the issuing of a number of documents that the agent must fill in in order to inform all interested parties. The main time of the vessels' stay in the port are cargo handling - loading and discharging operations. During this period, agency service includes non-stop control of cargo handling, considering the interests of the shipowner. The three stages of the process under consideration are formalized in their mutual dependence and mutual conditioning using the apparatus of temporal logic. Their clear coordination in time ensures the coordination of the process in general, because only the timeliness and correctness of each stage of the agency service process and its completion allow the next stage to begin. The presented process was formalized with the help of temporal logic operators, which can establish cause-and-effect relationships between the stages and ensure the continuity of the process and the interconnection of the stages themselves. A set of documents necessary for the start, execution and completion of each of the stages has been defined. Some of the documents are external to the ship agent, some are issued directly by him, but each of them is key in the implementation of certain operations in the process of agency service.